2005
DOI: 10.1089/end.2005.19.823
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Retroperitoneal Lymph-Node Dissection with the Waterjet Is Technically Feasible and Safe in Testis-Cancer Patient

Abstract: The waterjet allows the safe and complete removal of lymphatic tissue, leaving vulnerable anatomic structures intact. It can decrease the learning curve of laparoscopic RPLND and contribute to better acceptance of this procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 21 publications
0
5
0
1
Order By: Relevance
“…In the primary staging setting, several recent studies showed that L‐RPLND in expert hands is a possible procedure in the management of patients with testicular cancer who require surgery to address the retroperitoneal lymph nodes [75,76,82–88]. Rassweiler et al.…”
Section: Laparoscopic (L)‐rplndmentioning
confidence: 99%
“…In the primary staging setting, several recent studies showed that L‐RPLND in expert hands is a possible procedure in the management of patients with testicular cancer who require surgery to address the retroperitoneal lymph nodes [75,76,82–88]. Rassweiler et al.…”
Section: Laparoscopic (L)‐rplndmentioning
confidence: 99%
“…Early use of waterjet dissection has been reported in liver and kidney surgery. 10,30,31,34,35,52 Subsequently, waterjet dissection was used in orthopedic procedures, 8,9,16,41,48 urological and hepatic surgery, 2,45,56 parotid surgery, 18,47 ophthalmological surgery, 6,18,19,[53][54][55] with endovascular techniques, 20 and in thoracoabdominal surgery. 15,17 The first application of waterjet dissection in neurosurgery was reported by Terzis et al 51 in 1989.…”
mentioning
confidence: 99%
“…Hydrojet has been used during laparoscopy for more than 20 years. 12 Hydro-Jet dissection requires a special hydro-jet generator 13,14 and produces a high-pressure jet of between 20 to 60 BAR. The “original” hydro-jet systems forced the irrigant through a central cannula, and other methods also used an irrigation probe with a hypodermic needle type of tip.…”
Section: Discussionmentioning
confidence: 99%